2012
DOI: 10.1149/2.049212jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Conversion of Methanol and Carbon Dioxide to Dimethyl Carbonate at Graphite-Pt Electrode System

Abstract: Electrocatalytic activation and conversion of methanol and CO 2 to dimethyl carbonate with graphite and platinum electrodes in the dialkylimidazolium ionic liquid-methanol system was conducted under ambient conditions. Among the ionic liquids screened, 1-benzyl-3-methylimidazolium chloride (BzmimCl) exhibited effective performance as a supporting electrolyte. In the process of the electrolysis, dimethyl carbonate was effectively synthesized in the absence of any other additives. Based on the electrochemical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…In the past few years, the electrosynthesis of cyclic carbonates from epoxides and diols, and the production of organic carbamates from amines have been reported using ILs. The synthesis of dimethyl carbonate in the presence of ILs has also been the focus of special attention in the electrochemical field with Zhang et al and Feng and Liu, respectively, achieving 74 and 72% yields in the presence of [bmim][BF4] with a copper working electrode. To improve the yield in the same ionic liquid Feng et al and Wang et al used a nanoporous copper electrode based on platinum (NPC‐Pt) and silver (NPC‐Ag), slightly increasing the yield to 81 and 80%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the electrosynthesis of cyclic carbonates from epoxides and diols, and the production of organic carbamates from amines have been reported using ILs. The synthesis of dimethyl carbonate in the presence of ILs has also been the focus of special attention in the electrochemical field with Zhang et al and Feng and Liu, respectively, achieving 74 and 72% yields in the presence of [bmim][BF4] with a copper working electrode. To improve the yield in the same ionic liquid Feng et al and Wang et al used a nanoporous copper electrode based on platinum (NPC‐Pt) and silver (NPC‐Ag), slightly increasing the yield to 81 and 80%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Cyclic voltammetry was carried out with a CHI620B electrochemical analyzer. Before the measurement, Pt electrodes with rectangle and surface area 0.2826 cm 2 (Pt-213, Weiye instrument factory in Shanghai) were burnished with metallographic abrasive paper [W20(02)-500 # , Shanghai grinding wheels plant], followed by washing with acetone and distilled water in turn.…”
Section: Methodsmentioning
confidence: 99%
“…Reports have shown that ILs can act to stabilise the first electron reduction of the physically absorbed CO 2 by complexation of the reduction product with the IL cation. [13][14][15] Further studies used hydrated ILs, to provide a source of H + , CO 2 physically absorbed within the IL was reduced with Ag as working electrode which enabled further reduction of the IL stabilised [ CO 2 ]to CO as shown in the Scheme 1. Initial CO 2 electrochemical reduction experiments in ILs employed 1-alkyl-3methylimidazolium ([C n mim] + ) based ILs with a range of non-coordinating anions such as [BF 4 ] -, Br -, Cl -.…”
Section: Introductionmentioning
confidence: 99%